Generation of DNA-based markers in specific genome regions by two-primer RAPD reactions. - Hu, J; van Eysden, J; Quiros, C F (Genome Research, 1995)
Random amplified polymorphic DNA (RAPD) markers offer quick screening of different regions of the genome for genetic polymorphisms. The standard RAPD procedure uses a single 10-base-long random oligonucleotide as a primer to amplify short stretches of the genome by PCR. We modified the procedure by using two primers in each reaction in a Brassica napus mapping project. We found that the two-primer RAPD tends to amplify more and smaller fragments than the standard RAPD technique. These new bands were always amplified in the two-primer reactions, and Southern analysis revealed that they had no homology to the bands amplified in single-primer reactions involving the same primers. Furthermore, these new markers were not linked to markers amplified with the same primers in the standard RAPD reactions, suggesting that they were amplified from different genomic regions. The advantage of the two-primer RAPDs is that it allows more reactions to be carried out with a limited number of primers to generate more markers. Using a single primer, the number of reactions is equal to the number of primers (n), which in turn limits the total number of markers. When using two primers in all possible combinations, the total number of reactions increases to n x (n-1/2). This method could be useful in conjunction with bulked segregant analysis to develop high density maps of certain chromosomal regions. We used this approach to map a second marker linked to a gene governing low linolenic acid concentration in a B. napus F2 population.